Modern Ylide Chemistry Applications in Ligand Design, Organic and Catalytic Transformations (Structure and Bonding,, 2018)
This volume covers recent advances in the chemistry of ylidic compounds with focus on their application in the design of ligands with unique donor properties, the development of novel organic transformations as well as the use of ylides in homogenous catalysis. Thereby, this volume particularly aims at the community of organic and organometallic chemists engaged in synthetic chemistry and catalysis as well as in the use of special ligands for the stabilization of unusual main group element species and the "transition-metal free" activation of element-element/hydrogen bonds. These fields of research are highly active and vivid research areas to which ylide chemistry has only recently started to contribute, but has already led to fascinating developments in most different directions. This volume highlights these recent developments, thus giving not only an overview over the past achievements, but also possibilities for future applications. To this end, the chapters selected in this volume combine different aspects of ylide chemistry, starting with theoretical aspects in ligand design followed by synthetic organic methods, catalytic transformations and complex chemistry. .